Educational Philosophies of Advaita-Vedanta and Islam - Ahmad, Shamim (JOURNAL OF INDIAN EDUCATION, 2009)
This write-up deals with various shades of Advaita-Vedantic and Islamic philosophy. Main focus is on the ideological perspective of these two philosophies, viz a viz their relevance in the present world educational scenario. This is also a comparative study aimed to reconstruct and re-pattern the concept and methodology of education in consistence with our cultural heritage and challenges of time.